TERBITNYA SERTIFIKAT HAK ATAS TANAH AKIBAT PERALIHAN HAK YANG CACAT HUKUM - Tri Susilaningsih (University of Merdeka Malang, 2017)
The transfer of land rights is a process of transferring the right of ownership of one person lawfully and to the ownership of the new person forever as long as the rights are not transferred. Authentic deeds are the basis or evidence of such transfer of rights made by the land deed. The registration of the transfer of rights is a means of obtaining legal protection from the controlled land. The principle of land registration should reflect a thoroughness of ownership of the land and the rights of third parties affecting it. The transfer of rights as stated in the provisions of Government Regulation No. 10/1961 on Land Registration and Government Regulation No. 24/1997 on Land Registration. Submission by this Deed means that the ownership of the land has been transferred from the old owners of the new ownership and the new owner is obliged to register his land rights in the National Land Agency to obtain legal certainty and legal protection. The proof of ownership is a Certificate. There are times when the issuance of Certificates is due to the transfer of a right or legal disability ground.